Clinical applications of proton and carbon ion therapy - Rackwitz, Tilmann; Debus, Jürgen (Seminars in oncology, 2019)
Treatment of cancer patients with charged particles like proton and carbon ions landmarks a new era in high-precision medicine. This review aims to summarize the physical and biological advantages of charged particle beams over conventional photon irradiation, presents some highlights in the treatment of selected tumor entities, and gives an update on previous and ongoing clinical trials.